Sinonim (Mutaradif) dalam Pandangan Tokoh Klasik dan Modern (Kajian Sematik) - Nurul Hidayah (Menara Tebuireng, 2016)
Synonym is one study in linguistics is semantics. Existence of synonyms in linguistic studies into conflict between classical and modern leaders. Most of them reject their synonyms and others receive the keberaan. The purpose of this article to know the reasons and limits of such conflict. The method used to achieve these objectives is to use quantitative methods. As for the collection of data, the authors use a step through the collection of books related to synonyms. The results obtained in this study are each classical and modern character has its own reasons to accept or deny the existence of synonyms. Their differences lies in the nature of the synonym for each word